2021
DOI: 10.1093/jncics/pkab066
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Antigen 15-3/Mucin 1 Levels in CCTG MA.32: A Breast Cancer Randomized Trial of Metformin vs Placebo

Abstract: Background Circulating levels of CA 15–3, a tumor marker and regulator of cellular metabolism, were reduced by metformin in a non-randomized neoadjuvant study. We examine effects of metformin (vs placebo) on CA 15–3 in participants of MA.32, a Phase 3 randomized trial in early-stage breast cancer. Methods 3649 subjects with T1-3, N0-3, M0 breast cancer were randomized; pretreatment and 6 month on-treatment fasting plasma was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
1
4
0
1
Order By: Relevance
“…The findings reported herein are consistent with randomized trials that failed to identify a beneficial effect of metformin (in addition to standard chemotherapy or hormone therapy) on outcomes in patients with metastatic breast cancer without diabetes . These findings suggest the metabolic changes previously reported in this trial population and any potential direct antitumor effects of metformin were not sufficient to affect breast cancer outcomes . They underscore the need for well-conducted randomized trials prior to the clinical adoption of interventions that appear to benefit cancer when they are investigated in observational studies.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The findings reported herein are consistent with randomized trials that failed to identify a beneficial effect of metformin (in addition to standard chemotherapy or hormone therapy) on outcomes in patients with metastatic breast cancer without diabetes . These findings suggest the metabolic changes previously reported in this trial population and any potential direct antitumor effects of metformin were not sufficient to affect breast cancer outcomes . They underscore the need for well-conducted randomized trials prior to the clinical adoption of interventions that appear to benefit cancer when they are investigated in observational studies.…”
Section: Discussionsupporting
confidence: 83%
“…Prior to randomization, clinical and radiological assessments were required at diagnosis or later to rule out metastases; blood samples were collected to verify adequate kidney and liver function and to ensure that the fasting glucose value was 126 mg/dL or less. Patients provided consent for collection of tumor and normal breast tissue and fasting blood samples for analyses of metabolic and related factors as previously reported …”
Section: Methodsmentioning
confidence: 99%
“…A total of 41 RCTs (45 publications) evaluated the effect of MTF versus placebo/control on anthropometric variables; 16,17,46–88 23 RCTs included LSM as a co‐intervention in both arms and its definition was variable across RCTs. Five RCTs recommended a hypocaloric diet, defined as allowing 1300 to 1500 kcal/day or 25 kcal/kg ideal body weight.…”
Section: Resultsmentioning
confidence: 99%
“…Overexpression of CA 27-29 has been observed in breast cancer cells, particularly in advanced stages of the disease. Elevated serum levels of CA 27-29 have been associated with tumor burden and metastatic spread in breast cancer patients [34]. Several studies have shown that CA 27-29 levels may be useful for monitoring disease progression in patients with MBC and have shown that an increase in CA 27-29 levels may precede radiological evidence of disease progression, suggesting that it may serve as an early indicator of treatment failure or tumor recurrence.…”
Section: Serological Ca 27-29 Supporting Serological Monitoringmentioning
confidence: 99%